Exact Solutions for Nonlinear Differential Difference Equations in Mathematical Physics - Khaled A. Gepreel; Taher A. Nofal; Fawziah M. Alotaibi (Abstract and Applied Analysis)
We modified the truncated expansion method to construct the exact solutions for some nonlinear differential difference equations in mathematical physics via the general lattice equation, the discrete nonlinear Schrodinger with a saturable nonlinearity, the quintic discrete nonlinear Schrodinger equation, and the relativistic Toda lattice system. Also, we put a rational solitary wave function method to find the rational solitary wave solutions for some nonlinear differential difference equations. The proposed methods are more effective and powerful to obtain the exact solutions for nonlinear difference differential equations.